Healthy Eating: Super Sandwiches: FCS8699/FY711, rev. 7/2011 - Hillan, Jennifer; Minton, Emily (EDIS, 2011)
Sandwiches make quick, easy, and nutritious meals. And here are some tips to create new sandwich favorites! This revised 1-page fact sheet was written by Jennifer Hillan and Emily Minton and published by the UF Department of Family, Youth and Community Sciences, July 2011. FCS8699/FY711: Healthy Eating: Super Sandwiches (ufl.edu)